Nationwide population‐based study of cause‐specific death rates in patients with psoriasis. (9th June 2014) - Salahadeen, E.; Torp‐Pedersen, C.; Gislason, G.; Hansen, P.R.; Ahlehoff, O.
Abstract: Background: Psoriasis is a common chronic disease, mediated by type 1 and 17 helper T cell‐driven inflammation. Epidemiological studies have demonstrated a wide range of comorbidities and increased mortality rates. However, the current evidence on psoriasis‐related mortality is limited and nationwide data have not been presented previously. Methods: In a nationwide population‐based cohort we evaluated all‐cause and cause‐specific death rates in patients with psoriasis as compared to the general population. Results: The entire Danish population aged 18 and above, corresponding to a total of 5 458 627 individuals (50.7% female, 40.9 years ± 19.7), including 94 069 with mild psoriasis (53% female, 42.0 ± 17.0 years) and 28 253 with severe psoriasis (53.4% female, 43.0 ± 16.5 years), was included. A total of 884 661 deaths were recorded, including 10 916 in patients with mild psoriasis and 3699 in patients with severe psoriasis. The age at time of death varied by psoriasis status, i.e. 76.5 ± 14.0, 74.4 ± 12.8 and 72.0 ± 13.4 years, for the general population, mild psoriasis and severe psoriasis respectively. In general, the highest death rates were observed in patients with severe psoriasis. Overall death rates per 1000 patient years were 13.8 [confidence interval (CI) 13.8–13.8], 17.0 (CI 16.7–17.3) and 25.4 (CI 24.6–26.3) for the general population, patients with mild psoriasis and patients with severe psoriasis respectively. Conclusion: This nationwide population‐based study of cause‐specific death rates in patients with psoriasis demonstrated reduced lifespan and increased rates of all examined specific causes of death in patients with psoriasis compared to the general population.